2017
DOI: 10.1039/c7ee00899f
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the fill factor Shockley–Queisser limit in stable, dopant-free triple cation perovskite solar cells

Abstract: High fill factor, large area perovskite solar cells are realized with undoped organic transport layers by optimizing the charge carrier transit through PTAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
331
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(357 citation statements)
references
References 34 publications
16
331
0
Order By: Relevance
“…Further, the PL intensity is lower in 15 nm NiCo 2 O 4 film than that of the thicker films, pointing to an efficient suppression of the electron-hole recombination (Figure 5b, inset). The direct correlation of faster charge carriers extraction at thinner HTL layers with increased FF has been previously studied by Stolterfoht et al [77] We also notice that the configuration of 15 nm NiCo 2 O 4 HTL is depleted faster than the other devices due to enhanced charge carrier collection, which can also confirm the increase at the FF of the corresponding PVSC. Figure 6a shows the characteristic Nyquist plots of the three corresponding PVSCs devices for 15, 20, and 30 nm sized NiCo 2 O 4 films.…”
Section: Blade Coating Processed Thin Films Of Nico 2 O 4 Npssupporting
confidence: 84%
“…Further, the PL intensity is lower in 15 nm NiCo 2 O 4 film than that of the thicker films, pointing to an efficient suppression of the electron-hole recombination (Figure 5b, inset). The direct correlation of faster charge carriers extraction at thinner HTL layers with increased FF has been previously studied by Stolterfoht et al [77] We also notice that the configuration of 15 nm NiCo 2 O 4 HTL is depleted faster than the other devices due to enhanced charge carrier collection, which can also confirm the increase at the FF of the corresponding PVSC. Figure 6a shows the characteristic Nyquist plots of the three corresponding PVSCs devices for 15, 20, and 30 nm sized NiCo 2 O 4 films.…”
Section: Blade Coating Processed Thin Films Of Nico 2 O 4 Npssupporting
confidence: 84%
“…Furthermore, the aggregated LiTFSI can be hydrated by moisture in ambient conditions, leading to the decomposition of the perovskite surface. [47][48][49] Zhu et al reported that Li + migration from the HTM layer to the perovskite and TiO 2 layer deteriorated the interfaces in the solar cells, which resulted in a reduction of the V OC and FF compared to the Li-free cells. This is consistent with previous reports where the FF is closely related to the quality of the perovskite|HTM interface hindering Adv.…”
Section: Resultsmentioning
confidence: 99%
“…By replacing TiO2 with a low temperature SnO2 with higher charge selectivity for efficient electron extraction, a stabilized PCE of 20.8% could be obtained by a Cs + -doped FAMA perovskite [50]. For p-i-n solar cells, (CsPbI3)0.05[(FAPbI3)0.83(MAPbBr3)0.17]0.95 films on top of PTAA led to PCEs of 20% with a fill factor (close to 0.8) approaching the Shockley-Queisser limit [51]. Despite these results, the question remained whether one can fabricate highly efficient, mixed perovskite planar solar cells without an excess of PbI2.…”
Section: Mixed Perovskites In N-i-p and P-i-n Solar Cells: Is The Excmentioning
confidence: 94%